Implementasi Ajaran Tri Kaya Parisudha Dalam Pembelajaran Pendidikan Agama Hindu Dan Budi Pekerti di SD Taman Tirta - Budayasa, I Made Rai; Dharmawan, Kadek Agus (Metta : Jurnal Ilmu Multidisiplin, 2023)
Education is one very important aspect in educational life as a human effort to develop their personality in accordance with the values ​​that exist in society and culture in order to improve one's quality and be able to develop one's potential. As a reference for prospective teachers to conduct direct research in real situations, both in teaching activities and other teacher duties in accordance with national/institutional education standards, and to form children who are suputra (good, wise), sadha (religious/faithful), and gunawan (intelligent, skilled) in accordance with the teachings of Tri Kaya Parisudha. This research aims to: (1) Find out how the teaching of Hindu Religion and Moral Character is taught at Taman Tirta Elementary School, (2) Find out what the obstacles are in implementing the Tri Kaya Parisudha teachings in learning Hindu Religion and Character Education at Taman Tirta Elementary School, (3) Find out how Efforts made to face obstacles in implementing the Tri Kaya Parisudha teachings in teaching Hindu Religion and Character education at Taman Tirta Elementary School. Data collection techniques are observation, interviews, documentation and literature study. The data that has been collected is analyzed using the Qualitative Descriptive analysis method with reduction steps, data presentation, drawing conclusions. The results of the research show that: (1) Learning the Tri Kaya Parisudha and Good Character at Taman Tirta Elementary School is divided into: Planning, Implementation and Evaluation (2) Obstacles to Learning the Tri Kaya Parisudha and Good Character at Taman Tirta Elementary School, namely: Environmental constraints, Constraints from parties teachers and obstacles on the part of students, (3) Efforts in dealing with obstacles in learning Tri Kaya Parisudha and Characteristics at Taman Tirta Elementary School are divided into three, namely: Providing relief in learning, preventing levels of frustration from arising, instilling the teachings of Tri Kaya Parisudha.